Psychoeducation for breast cancer: A systematic review and meta-analysis. (April 2022) - Setyowibowo, Hari; Yudiana, Whisnu; Hunfeld, Joke A.M.; Iskandarsyah, Aulia; Passchier, Jan; Arzomand, Homra; Sadarjoen, Sawitri S.; de Vries, Ralph; Sijbrandij, Marit
Abstract: Background: Psychoeducation has emerged as an intervention for women with breast cancer (BC). This meta-analysis evaluated the effectiveness of psychoeducation on adherence to diagnostic procedures and medical treatment, anxiety, depression, quality of life (QoL), and BC knowledge among patients with BC symptoms or diagnosis and BC survivors. Methods: A systematic literature search (in PubMed, Embase, PsycINFO and Cochrane) for randomised controlled trials (RCTs) comparing the effects of psychoeducation to control among patients with BC symptoms or diagnosis and BC survivors. Effects were expressed as relative risks (RRs) and standardized mean differences (SMDs) with their 95% confidence intervals. Results: Twenty-seven RCTs (7742 participants; 3880 psychoeducation and 3862 controls) were included. Compared with controls, psychoeducation had no significant effect on adherence to diagnostic procedures and medical treatment (RR 1.553; 95% CI 0.733 to 3.290, p = .16), but it significantly decreased anxiety (SMD -0.710, 95% CI -1.395 to −0.027, p = .04) and improved QoL with (SMD 0.509; 95% CI 0.096 to 0.923, p < .01). No effects were found for psychoeducation on depression (SMD -0.243, 95% CI -0.580 to 0.091, p = .14), or BC knowledge (SMD 0.718, 95% CI -0.800 to 2.236, p = .23). Conclusion: We demonstrated that psychoeducation did not improve adherence to diagnostic procedures and treatment, depression and BC knowledge but was valuable for reducing anxiety and improving QoL. Future studies may explore the effectiveness of psychoeducation in promoting adherence across various types of cancer. Highlights: Psychoeducation is a promising intervention to help patients throughout the breast cancer care pathway. Psychoeducation, especially when delivered face-to-face and over an extended duration, was effective in reducing anxiety and improving Quality of life. Psychoeducation should be delivered in multiple sessions and the delivery method should be adapted to fit in with the local context, and may include group discussions, individual consultations, or interactive materials.